Seed coat color, weight and eye pattern inheritance in gamma-rays induced cowpea M2-mutant line - Reda M. Gaafar; Marwa Hamouda; Abdelfattah Badr (Journal of Genetic Engineering and Biotechnology, 2016)
Gamma radiation is a very effective tool for inducing genetic variation in characters of many plants. Black seeds of M2 mutant were obtained after exposure of an Egyptian cowpea cultivar (Kaha 1) to a low dose of gamma rays. Segregation of seed coat color, weight of 100 seeds and seed eye pattern of the black seeds of this mutant line were further examined in this study. Four colors were observed for seed coat in the M3 plants ranging from cream to reddish brown and three eye patterns were distinguished from each other. SDS–PAGE of the seed storage proteins showed 18 protein bands; five of these bands disappeared in the seeds of M3 plants compared to M2 and M0 controls while other 5 protein bands were specifically observed in seeds of M3 plants. PCR analysis using twelve ISSR primers showed 47 polymorphic and 8 unique amplicons. The eight unique amplicons were characteristic of the cream coat color and brown wide eye pattern (M03-G10) while the polymorphic bands were shared by 6 coat-color groups. A PCR fragment of 850 bp was amplified, using primer HB-12, in M3-G04 which showed high-100 seed weight. These results demonstrated the mutagenic effects of gamma rays on seed coat color, weight of 100 seeds and eye pattern of cowpea M3 mutant plants.